A Phase I Trial of the IGF‐1R Antibody Ganitumab (AMG 479) in Combination with Everolimus (RAD001) and Panitumumab in Patients with Advanced Cancer. (23rd March 2018) - Vlahovic, Gordana; Meadows, Kellen L.; Hatch, Ace J.; Jia, Jingquan; Nixon, Andrew B.; Uronis, Hope E.; Morse, Michael A.; Selim, M. Angelica; Crawford, Jeffrey; Riedel, Richard F.; Zafar, S. Yousuf; Howard, Leigh A.; et al.
Abstract : Purpose: This study evaluated the maximum tolerated dose or recommended phase II dose (RPTD) and safety and tolerability of the ganitumab and everolimus doublet regimen followed by the ganitumab, everolimus, and panitumumab triplet regimen. Materials and Methods: This was a standard 3 + 3 dose escalation trial. Doublet therapy consisted of ganitumab at 12 mg/kg every 2 weeks; doses of everolimus were adjusted according to dose‐limiting toxicities (DLTs). Panitumumab at 4.8 mg/kg every 2 weeks was added to the RPTD of ganitumab and everolimus. DLTs were assessed in cycle 1; toxicity evaluation was closely monitored throughout treatment. Treatment continued until disease progression or undesirable toxicity. Pretreatment and on‐treatment skin biopsies were collected to assess insulin‐like growth factor 1 receptor and mammalian target of rapamycin (mTOR) target modulation. Results: Forty‐three subjects were enrolled. In the doublet regimen, two DLTs were observed in cohort 1, no DLTs in cohort −1, and one in cohort −1B. The triplet combination was discontinued because of unacceptable toxicity. Common adverse events were thrombocytopenia/neutropenia, skin rash, mucositis, fatigue, and hyperglycemia. In the doublet regimen, two patients with refractory non‐small cell lung cancer (NSCLC) achieved prolonged complete responses ranging from 18 to >60 months; one treatment‐naïve patient with chondrosarcoma achieved prolonged stable disease >24 months. In dermal granulation tissue, the insulin‐like growth factor receptor and mTOR pathways were potently and specifically inhibited by ganitumab and everolimus, respectively. Conclusion: The triplet regimen of ganitumab, everolimus, and panitumumab was associated with unacceptable toxicity. However, the doublet of ganitumab at 12 mg/kg every 2 weeks and everolimus five times weekly had an acceptable safety profile and demonstrated notable clinical activity in patients with refractory NSCLC and sarcoma. Implications for Practice: This trial evaluated the maximum tolerated dose or recommended phase II dose and safety and tolerability of the ganitumab and everolimus doublet regimen followed by the ganitumab, everolimus, and panitumumab triplet regimen. Although the triplet regimen of ganitumab, everolimus, and panitumumab was associated with unacceptable toxicity, the doublet of ganitumab at 12 mg/kg every 2 weeks and everolimus at five times weekly had an acceptable safety profile and demonstrated notable clinical activity in patients with refractory non‐small cell lung cancer and sarcoma. Abstract : This article reports a phase I dose‐escalation study conducted to determine the maximum tolerated dose and recommended phase II dose and to preliminarily evaluate the clinical activity of everolimus (RAD001), ganitumab (AMG 479), and the EGFR inhibitor panitumumab (the RAP trial) in advanced solid tumors.